2012
DOI: 10.1074/jbc.m111.337196
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Metabolomics Analysis of Glioblastoma Subtypes

Abstract: Background: Unpredictable clinical behavior of glioblastoma multiforme suggests distinct molecular subtypes. Results: Metabolic profiles of different glioblastoma lines indicate distinct subtypes correlated with gene expression differences. Conclusion: A subset of metabolites can be used to distinguish between four subtypes of glioblastomas. Significance: Metabolic profiling of cancers provides a way for subtype determination with possible diagnostic and prognostic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 26 publications
7
54
0
1
Order By: Relevance
“…Interestingly, most of the glioma cell lines assessed for ATX protein expression tested positive, which is in line with a previous study that screened for ATX expression in 50 cultured human tumor cell lines and found high ATX expression in most brain cancer cell lines 37. Besides elevated ATX levels, LN229 also shows high PDGFRα levels 38. This molecular characteristic of LN229 most likely contributes to its cancerous phenotypic properties as PDGFRα signaling promotes cell proliferation and motility in glioblastomas 39.…”
Section: Resultssupporting
confidence: 85%
“…Interestingly, most of the glioma cell lines assessed for ATX protein expression tested positive, which is in line with a previous study that screened for ATX expression in 50 cultured human tumor cell lines and found high ATX expression in most brain cancer cell lines 37. Besides elevated ATX levels, LN229 also shows high PDGFRα levels 38. This molecular characteristic of LN229 most likely contributes to its cancerous phenotypic properties as PDGFRα signaling promotes cell proliferation and motility in glioblastomas 39.…”
Section: Resultssupporting
confidence: 85%
“…Cuperlovic-Culf et al [59] investigated nine human glioma cell lines' (A172, BS149, Hs683, LN18, LN229, LN319, LN405, U343MG, U373) metabolome. The 1 H NMR spectroscopy analysis of the intracellular levels of metabolites allowed four groups with distinct metabolic profiles to be distinguished.…”
Section: Metabolomic Studies In Gliomasmentioning
confidence: 99%
“… Zahl der nachweisbaren und quantifizierbaren Metabolite mit ≥50 % Häufigkeit in den 1 H‐NMR‐Spektren verschiedener biologischer Flüssigkeiten [Urin, Serum, Speichel, Rückenmarkflüssigkeit, Kondensat der Ausatemluft, Faecesextrakte, Zelllysate (z. B. Ovarial‐ und Glioblastomzellen) und intakten Geweben (z. B. Leber und Pankreas) [25, 26] ].…”
Section: Metabolomik Mit Nmrunclassified